Pengaruh Stres Kerja dan Kompensasi Terhadap Kinerja Karyawan dengan Lingkungan Kerja Sebagai Pemediasi Pada CV. Amanda Brownies - Araf, Moh.; Akob, Muh.; Alam, Syamsul (Papanda Publisher, 2024)
This study aims to determine the direct effect of work stress, compensation and work environment on employee performance. The direct effect of work stress and compensation on the work environment. The indirect effect of work stress and compensation variables on employee performance with the work environment as a mediator variable at CV. Amanda Brownies. Data collection using primary data obtained from questionnaires using saturated samples. The population in this study was 39 respondents. The results of the questionnaire have been tested for validity and reliability using the PLS model scheme and model evaluation, inner model evaluation with determinant coefficient tests, model goodness of fit tests and hypothesis tests both directly and indirectly. The results of this data processing use SmartPLS version 3. The results of the study directly show that the variables of work stress and compensation have a positive and significant effect on the work environment. The work environment and compensation have a positive and significant effect on employee performance, work stress does not affect employee performance. The results of the study indirectly show that work stress has a positive and significant effect on employee performance with the work environment as a mediator and compensation does not affect employee performance with the work environment as a mediator.